A correlation analysis between clinical manifestations, therapeutic strategies, and the prognosis of children with cryptococcal meningitis in China. (June 2020) - Yang, Haiyan; Yin, Fei; Xiao, Ting; Gan, Siyi; Pan, Zou; Peng, Jing; Wu, Liwen
Highlights: Factors related to a poor prognosis in cryptococcal meningitis included cerebral hernia, consciousness disorder, visual impairment, hydrocephalus, and an intracranial pressure >300 mmH2 O in the cerebrospinal fluid. In the drug treatment scheme, amphotericin B combined with flucytosine is superior to single drug therapy, and whether or not the application of intrathecal administration had little effect on prognosis. Early surgical intervention with internal drainage is the key factor to improve the prognosis, especially to reduce visual impairment sequelae. A positive result for Cryptococcus in the CSF before surgery is not a contraindication to surgery. Abstract: Objective: This aim of this study was to analyze the correlations between clinical manifestations, treatment strategies, and the prognosis in cryptococcal meningitis (CM) in China. Methods: This was a retrospective analysis of the clinical data of CM patients treated during the years 2002–2019. The clinical features and supplementary examinations, treatment strategies, and prognosis were summarized and then a correlation analysis was performed. Results: Fifty patients were enrolled. The most common symptoms were fever, headache, and vomiting. Five of these patients died and five had visual impairment sequelae; nine of these patients were treated before 2010. Correlation analysis suggested that cerebral hernia, consciousness disorder, visual impairment, hydrocephalus, and an intracranial pressure >300 mmH2 O in cerebrospinal fluid (CSF) were associated with a poor prognosis. Whether or not the application of intrathecal administration had little effect on prognosis. Early surgical intervention with internal drainage helped to reduce the mortality and incidence of visual impairment sequelae, whether or not Cryptococcus was present in the CSF before surgery. Conclusions: Clinically, the presence of a cerebral hernia, consciousness disorder, hydrocephalus, visual impairment, or intracranial pressure >300 mmH2 O often indicates a poor prognosis in patients with CM. The prognosis improved significantly after 2010, following an adjustment of the treatment strategy. Early internal drainage is the key factor, and CSF positive for Cryptococcus before surgery is not a contraindication.